2016
DOI: 10.1093/eurheartj/ehw171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single dose of the interleukin-6 receptor antagonist tocilizumab on inflammation and troponin T release in patients with non-ST-elevation myocardial infarction: a double-blind, randomized, placebo-controlled phase 2 trial

Abstract: Tocilizumab attenuated the inflammatory response and primarily PCI-related TnT release in NSTEMI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
237
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 307 publications
(252 citation statements)
references
References 22 publications
8
237
3
4
Order By: Relevance
“…The design of the trial has been described previously 9. Patients between 18 and 80 years of age with NSTEMI presumed to be caused by CAD were eligible for inclusion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design of the trial has been described previously 9. Patients between 18 and 80 years of age with NSTEMI presumed to be caused by CAD were eligible for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…In ACS, elevated levels of IL-6 and C reactive protein (CRP), the latter at least partly induced by IL-6,8 are related to adverse outcomes and the degree of myocardial injury 4. Furthermore, IL-6 seems to contribute to ischaemia/reperfusion injury in these patients 9. IL-6 is also associated with endothelial dysfunction in ACS,2 and may also contribute to enhanced expression of markers of endothelial cell activation such as cellular adhesion molecules (CAMs)10 and von Willebrand factor (vWF) 11.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting both the mPTP and improving plaque stability could be a strategy. Blocking IL-6, known to destabilize plaque in acute coronary syndromes, with the IL-6 receptor monoclonal antibody, tocilizumab, that also targets the mitochondria, has been shown to reduce infarct size in patients with non-ST-segment elevation myocardial infarction [54]. …”
Section: Discussionmentioning
confidence: 99%
“…19 Results from these trials showed a decrease in early CRP and troponin T release (a measure of myocardial damage), although coronary flow reserve (a measure of coronary microvascular function) was unaffected when assessed 6 months later. 19,20 The LDL cholesterol lowering drug Alirocumab (Praluent), 10 is also being tested in phase IV trials for use in non-ST segment elevation MI patients (NSTEMI) that have previously responded poorly to statins. Alirocumab will be administered as a single dose in acute MI, and LDL cholesterol and inflammatory markers measured up to 14 days after infarct.…”
Section: Myocardial Infarctionmentioning
confidence: 99%